Towards a transferable nonelectrostatic model for continuum solvation: The electrostatic and nonelectrostatic energy correction model. Issue 20 (9th June 2022) - Vassetti, Dario; Labat, Frédéric
Abstract: In this work, we introduce an electrostatic and non‐electrostatic (ENE) correction to the solvation energy based on the Solvent‐Accessible Surface Area (SASA) of the solute and the solvent static dielectric constant. The proposed correction was developed for neutral solutes in non‐aqueous solvents, considering three different implicit solvation models based on a Self‐Consistent Reaction Field treatment of solute‐solvent mutual polarization using an Apparent Surface Charge formalism, namely the Integral Equation Formalism of the Polarizable Continuum Model using a continuous surface charge scheme (PCM), the Solvation Model based on solute electron density (SMD), and the generalized Finite‐Difference Poisson‐Boltzmann (FDPB) model. The proposed correction was parametrized on a diverse training set of 4980 solvation data from the Solv@tum database of experimental solvation energies, and validated on the non‐aqueous subset of the MNSOL database comprising 2140 solvation energies. The performances of the proposed ENE models with minimal and extended parameters formulations have been analyzed and the latter variant has been further compared to the widely used Cavity, Dispersion, and Solvent structural effects (CDS) non‐electrostatic model originally developed for the SMx family of implicit solvation models. Overall, a very good agreement between the computed solvation energies with the ENE correction and the reference experimental data has been found on both the training and test sets for all continuum solvation models considered. Furthermore, results for the ENE correction are on par with the reference CDS non‐electrostatic model for both SMD and FDPB electrostatics, but with the advantage of using a lower number of parameters and thus an improved transferability between different electrostatics treatments. Abstract : We introduce an electrostatic and non‐electrostatic correction to the solvation energy based on the Solvent‐Accessible Surface Area of the solute and the solvent dielectric constant developed for neutral solutes in non‐aqueous solvents. Three implicit solvation models based on a Self‐Consistent Reaction Field using an Apparent Surface Charge formalism have been considered: the Integral Equation Formalism Polarizable Continuum Model (PCM), the Solvation Model based on solute electron density (SMD), and the generalized Finite‐Difference Poisson‐Boltzmann (FDPB) model.